2018
DOI: 10.1177/0018720818769260
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Human Steering Behavior During Path Following in Teleoperation of Unmanned Ground Vehicles

Abstract: The established model is a suited candidate to be used in place of human drivers for simulation-based studies of UGV mobility in teleoperation systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…If the cognitive models can be extended to shared control modes, in which teleoperators share the control authority with onboard autonomy, then the models can benefit the development and evaluation of semiautonomous solutions, as well. Mirinejad et al (2018) have shown that speed can have a strong impact on the ALKE performance in constant speed settings. In this work, Lower tailed hypothesis at 2 σ .005…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…If the cognitive models can be extended to shared control modes, in which teleoperators share the control authority with onboard autonomy, then the models can benefit the development and evaluation of semiautonomous solutions, as well. Mirinejad et al (2018) have shown that speed can have a strong impact on the ALKE performance in constant speed settings. In this work, Lower tailed hypothesis at 2 σ .005…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that human operation behavior varies under different driving conditions for teleoperation, such as different communication delays and vehicle speeds (Mirinejad et al, 2018). Similarly, a set of control gains that is able to describe the human operator behavior under a certain teleoperation condition may not capture the human operator behavior under a different condition.…”
Section: Model Tuningmentioning
confidence: 99%
See 3 more Smart Citations